On the Sense and Practicability of Ascribing Moral Responsibility to Corporations – An Overview - Kwarciński, Tomasz (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2016)
The article seeks to determine if corporations can be expected to act in a morally responsible manner and what possible factors can make such a view sensible. The article systematises views on corporate moral responsibility. Those views range widely. They include the perspective that CSR is not possible through the belief that such responsibility is based on an appropriately understood conception of moral corporate subjectivity, to the view that it is not necessary to acknowledge a corporation’s moral subjectivity in order to assign it moral responsibility.